Territories, region and social imaginaries in about: the building of the foundational historic discourses of Villa Nueva and Villa María (provin-cia de Córdoba, Argentina) - Barrera Calderón, Emanuel (Universidad Nacional del Litoral, 2020)
The cities of Villa Nueva and Villa María are located on each bank of the Ctalamochita riverbed in the southeast of the province of Córdoba (Argentina). This area has been an enclave where the route of the Camino Real passed and which later would be the confluence of different railways and national and provincial routes. Being adjoining cities, the historical discourses based on the foundational moments of these, were constituted by resorting to the antagonism around the Progreso–Tradition duality represented in other so many social imaginaries. That is to say, the idea of Villa María underlies as a thriving and planned city from its bases and Villa Nueva understood as detained in time, backward, with conservative and clerical features. The objective is to analyze how historical discourses on the foundational past of both cities construct (or not) social imaginaries around a territory with regional identity. This will be through discourse analysis of a corpus of study integrated by the historiography in question.